2014
DOI: 10.1371/journal.pone.0086420
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Three Different (-135°C) Whole Body Cryotherapy Exposure Durations on Elite Rugby League Players

Abstract: BackgroundWhole body cryotherapy (WBC) is the therapeutic application of extreme cold air for a short duration. Minimal evidence is available for determining optimal exposure time.PurposeTo explore whether the length of WBC exposure induces differential changes in inflammatory markers, tissue oxygenation, skin and core temperature, thermal sensation and comfort.MethodThis study was a randomised cross over design with participants acting as their own control. Fourteen male professional first team super league r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 32 publications
5
52
0
2
Order By: Relevance
“…Core temperature has previously been shown to display a predictable relationship with T sk following WBC [8] and this would be an interesting area for future study in order to further explain the findings reported here. Further research using a measure of core temperature such as a rectal probe or temperature-sensitive ingestible capsule would be needed to make those comparisons, which were not available for this study.…”
Section: Discussionmentioning
confidence: 70%
“…Core temperature has previously been shown to display a predictable relationship with T sk following WBC [8] and this would be an interesting area for future study in order to further explain the findings reported here. Further research using a measure of core temperature such as a rectal probe or temperature-sensitive ingestible capsule would be needed to make those comparisons, which were not available for this study.…”
Section: Discussionmentioning
confidence: 70%
“…Additionally, another study demonstrated that 5 d of cryotherapy (−110°C for 2 min) after a normal daily training program (3 hours) in highly trained athletes induced an increase in anti-inflammatory interleukin-10 and a decrease in the pro-inflammatory interleukin-8 and interleukin-2, suggesting that cryotherapy improves recovery after exercise by reducing the inflammatory response 72 . In contrast, 2 minutes of cryotherapy (−135°C) did not impact on plasma interleukin-6 levels after a competitive elite rugby match 73 . Although the effects of cryotherapy on the inflammatory response were not consistent, post-exercise cryotherapy seems to attenuate inflammatory response after exercise.…”
Section: Post-coolingmentioning
confidence: 85%
“…Subjective and objective recovery variables, used to quantify recovery of EIMD, are delayed onset of muscle soreness (DOMS), reduced maximum voluntary isometric contraction (MVIC), vertical jump performance (VJP), and muscle swelling . Non‐invasive measures such as muscle oxygen saturation (SmO 2 ), cutaneous vascular conductance (CVC), mean arterial pressure (MAP), and skin temperature have been used to explain the possible blood flow and temperature‐induced physiological effects of cooling on recovery …”
Section: Introductionmentioning
confidence: 99%